A T-cell adult acute lymphoblastic leukemia harboring a rare near-tetraploid karyotype - Vrushali Raut; Harshit Khurana; Barun Kumar Chakrabarty; Bhushan Asthana (Iraqi Journal of Hematology, 2023)
Blast ploidy is a distinctive cytogenomic feature related to the prognostic outcome of acute lymphoblastic leukemia (ALL) patients. Near tetraploidy (NT) (81–103 chromosomes) is a very rare ploidy anomaly in (ALL). It is observed in approximately 1% of childhood B-cell precursor ALL (BCP-ALL). In T-ALL specifically in adult T-ALL, it is furthermore rare entity. Only few case reports are found in the existing literature. Compared to BCP-ALL, T-ALL lacks recurrent genetic anomalies with independent prognostic value. Although B-cell ALL associated with NT is related to a standard cytogenomic risk, the prognostic outcome of NT in T-cell ALL is yet to be determined. Conventional karyotyping of this entity is difficult to perform and interpret. Thus, it is recommended that karyotype results should be supplemented by fluorescence in situ hybridization. Herewith, we present an adult T-ALL case detected with NT karyotype with emphasis on prognostic significance.